Bioinspired, Ultrastrong, Highly Biocompatible, and Bioactive Natural Polymer/Graphene Oxide Nanocomposite Films. Issue 34 (19th June 2015) - Zhu, Wen‐Kun; Cong, Huai‐Ping; Yao, Hong‐Bin; Mao, Li‐Bo; Asiri, Abdullah M.; Alamry, Khalid A.; Marwani, Hadi M.; Yu, Shu‐Hong
<x xml:space="preserve">Abstract</x> Tough and biocompatible nanocomposite films: A new type of bioinspired ultrastrong, highly biocompatible, and bioactive konjac glucomannan (KGM)/graphene oxide (GO) nanocomposite film is fabricated on a large scale by a simple solution‐casting method. Such KGM–GO composite films exhibit much enhanced mechanical properties under the strong hydrogen‐bonding interactions, showing great potential in the fields of tissue engineering and food package.